Exploration of Changing Dynamics of Small House Spatiality: From Minimised Space Usage to Dynamic Living Space - Arslan, Ayça (Eastern Mediterranean University EMU, 2017)
In this thesis study, the changing spatialities of today’s small houses are studied and analyzed together with the changes in the structure of small households, by the diversities and dualities they have in the dynamics of spatiality which is different from traditional space organizations. As a new concept, small as living spaces has been examined from past to present by traditions and ideologies in relation with dynamics of small household structures and at the end the dynamic spatiality of recent day small houses has been focused in the comprehensive fieldwork of the research. Therefore, today’s small houses are handled together with today’s small household structures and today’s wide variety of small residential spaces with dimensions ranging from 20-100 m2 and with diverse concepts from minimum size usage to relevantly bigger living spatialities. In this context, the thesis firstly introduces the dynamics of small household structures with diversities and dualities in it and recent day lifestyles to understand better the wide variety of small houses spatiality today. In addition, studies and researches of TAYA (2011) (Türkiye Aile Yapısı Araştırma ve Öneriler) have been used to determine recent day situation of small households in Turkey as statistical, current and comprehensive data. In this context, study will focus on the spatiality of today’s small houses in the light of literary research in order to new concept based spatial relations such as; depth (dynamic relations), density (diverse relations), interpenetration (dual relations) and spatial identifiers linking these spatialities such as; transparency (perforated divider), conceal furniture (mobility), soft divisions (movable separators) finally reveal new space types and group spaces as compartments with integrated and implicit organizations. Therefore, in order to investigate these spatial concept (values and definitions) and inventions in the thesis study, space syntax and shape grammar methods were used together to measure conceptual findings with analytical results and consequently the gradation and dynamics of the varying spatialities in today’s small houses were tested by a triple method as spatial / space syntax / shape grammar. Keywords: Small houses, spatiality, space syntax, shape grammar, small household dynamics, space organization.

ÖZ: Bu tez çalışmasında, günümüz küçük konutlarında ki mekânsal değişimler, geleneksel mekan organizasyonlarından farklı mekansallık dinamiklerinde sahip oldukları çeşitlilik ve ikilemlerle, küçük hane halklarının yapısındaki değişikliklerle birlikte incelemekte ve analiz edilmektedir. Yeni bir konsept olarak, küçük yaşama alanları, geçmişten günümüze, küçük hane halkı yapılarının dinamiğiyle ilişkili olarak gelenek ve ideolojilerde incelenmiş ve sonunda, günümüze ait küçük konutların dinamik mekansallığı, araştırmanın ana saha çalışmasını yaratmıştır. Bu nedenle, günümüzün küçük hane halkı yapılarıyla ve bugünkü geniş yelpazeli 20-100 m2 arasında değişen küçük boyutlu yerleşim alanlarıyla ve aslen minimum mekan kullanımı ile maksimum alanlı büyük yaşam mekanları arasındaki çeşitli kavramlarla bir araya getirilmektedir. Bu bağlamda, tez önce küçük evlerin mekânsal özelliklerini daha iyi anlamak için, çeşitlilik ve ikilemleri olan küçük konut yapılarının dinamikleri ile günümüzdeki yaşam biçimlerini ortaya koymaktadır. Ayrıca, TAYA (2011) (Türkiye Aile Yapısı Araştırma ve Öneriler) tarafından yapılan araştırmalar, çalışmalar ve veriler, Türkiye’de günümüz küçük hane halkı yapısı incelemelerinde özellikle güncel, istatiksel ve kapsamlı bir veri olarak kullanılmıştır. Bu bağlamda, çalışmada yeni konsept temelli mekânsal ilişkilere yönelik olarak araştırmalar ışığında günümüz küçük konutlarının mekansallığına odaklanacaktır; derinlik (dinamik ilişkiler), yoğunluk (varyasyonlu ilişkiler), içiçe geçiş (ikili ilişkiler) mekânsal ilişkileri ve bunları birbirine bağlayan mekânsal tanımlayıcılar; geçirgen bölücüler, mobil değişen dönüşen ekipmanlar ve kaldırılabilir sökülebilir bölücüler tanımlanacaktır. Bu bağlamda, bu kavramsal bulguları analitik sonuçlar ile araştırmak için mekan sentaksı ve biçim grameri yöntemleri birlikte kullanılarak, tez çalışmasında ki kavramsal yaklaşımlar ve buluşlar ortaya koyulmuş ve günümüz küçük konutlarının değişen mekanların derecelendirilmesi ve dinamikleri; mekânsal / mekan sentaksı / biçim grameri ile üçlü bir yöntem ile incelenmiştir. Anahtar kelimeler: Günümüz küçük konutları, mekansallık, mekan sentaksı, çağdaş yaşam stilleri, mekan organizasyonu.
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2017. Supervisor: Assoc. Prof. Dr. Türkan Ulusu Uraz.
Keywords: Architecture; Architecture; Domestic-Small Houses; Small Housing-Architecture and Design; Small houses; spatiality; space syntax; shape grammar; small household dynamics; space organization